Role of cannabinoid cb1 receptors in the nucleus accumbens core in stress-induced reinstatement of cocaine seeking and context-specific increase of extracellular glutamate - Guzman, Andrea Susana (2022)
Fil: Guzmán, Andrea Susana. Universidad Nacional de Córdoba. Facultad de Ciencias Químicas, Argentina.